Nutrient deficiencies impact on the cellular and metabolic responses of saxitoxin producing Alexandrium minutum: A transcriptomic perspective - Akbar, Muhamad Afiq; Mohd Yusof, Nurul Yuziana; Usup, Gires; Ahmad, Asmat; Baharum, Syarul Nataqain; Bunawan, Hamidun (Human Resources Management Academic Research Society (HRMARS), 2023)
Dinoflagellate Alexandrium minutum Halim is commonly associated with harmful algal blooms (HABs) in tropical marine waters due to its saxitoxin production. However, limited information is available regarding the cellular and metabolic changes of A. minutum in nutrient-deficient environments. To fill this gap, our study aimed to investigate the transcriptomic responses of A. minutum under nitrogen and phosphorus deficiency. The induction of nitrogen and phosphorus deficiency resulted in the identification of 1049 and 763 differently expressed genes (DEGs), respectively. Further analysis using gene set enrichment analysis (GSEA) revealed 702 and 1251 enriched gene ontology (GO) terms associated with nitrogen and phosphorus deficiency, respectively. Our results indicate that in laboratory cultures, nitrogen deficiency primarily affects meiosis, carbohydrate catabolism, ammonium assimilation, ion homeostasis, and protein kinase activity. On the other hand, phosphorus deficiency primarily affects the carbon metabolic response, cellular ion transfer, actin-dependent cell movement, signalling pathways, and protein recycling. Our study provides valuable insights into biological processes and genes regulating A. minutum’s response to nutrient deficiencies, furthering our understanding of the ecophysiological response of HABs to environmental change.